Lucky Days with Mr. and Mrs. Green - Baker, Keith 1953- (Orlando, Fla. : Harcourt, 2005)
Mr. and Mrs. Green, a loving alligator couple, try their hand at detective work, a gumball-guessing contest, and the town talent show.
"Book three."
Keywords: Lost and found possessions -- Fiction; Contests -- Fiction; Talent shows -- Fiction; Alligators -- Fiction; Humorous Stories; Early chapter book